Paraprostatic cyst in a dog - Canpolat, I.; Eroksuz, Y. (My University, 2008)
A case of paraprostatic cyst in a dog is reported. The exact histological nature of the cyst was determined by post mortem examination as a praprostaticcyst of prostatic origin.
Keywords: Canis familiaris